2006
DOI: 10.1183/09031936.06.00001506
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin increases phagocytosis of apoptotic bronchial epithelial cells by alveolar macrophages

Abstract: Chronic obstructive pulmonary disease (COPD) is associated with increased apoptosis and defective phagocytosis in the airway. As uncleared cells can undergo secondary necrosis and perpetuate inflammation, strategies to improve clearance would have therapeutic significance. There is evidence that the 15-member macrolide antibiotic azithromycin has antiinflammatory properties. Its effects may be increased in the lung due to its ability to reach high concentrations in alveolar macrophages (AMs).The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
154
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(170 citation statements)
references
References 35 publications
13
154
0
3
Order By: Relevance
“…A flow-cytometric efferocytosis assay was performed using alveolar macrophages from BAL as previously reported 5,14 . Briefly immortalized normal bronchial epithelial cells (16HBE) were induced to undergo apoptosis using UV radiation for 20 min then stained with mitotracker red (MTR) (50L, 25g/mL) and used as phagocytic targets.…”
Section: Efferocytosis Of Apoptotic Bronchial Epithelial Cells By Alvmentioning
confidence: 99%
“…A flow-cytometric efferocytosis assay was performed using alveolar macrophages from BAL as previously reported 5,14 . Briefly immortalized normal bronchial epithelial cells (16HBE) were induced to undergo apoptosis using UV radiation for 20 min then stained with mitotracker red (MTR) (50L, 25g/mL) and used as phagocytic targets.…”
Section: Efferocytosis Of Apoptotic Bronchial Epithelial Cells By Alvmentioning
confidence: 99%
“…We found that airway macrophages from cigarette smokers and COPD subjects have a reduced ability to phagocytose bacteria, including NTHi (Hodge et al. 2006; Ween et al. 2016) which can potentially give rise to increased lung infections such as pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, CR3, CD14, CD31, CD36, CD44, LRP, vitronectin receptor, and the phosphatidylserine receptor have been previously observed to be expressed on human AMs (24,(49)(50)(51)(52), and MERTK has been noted to be expressed on cultured blood monocytes, the cells from which AMs are derived (5). In the present study, expression by MERTK by AMs was observed by microarray, TaqMan RT-PCR, immunocytochemistry, Western analysis, and flow cytometry.…”
Section: Expression Of Mertk On Amsmentioning
confidence: 99%